(NrEZNQ W sMIRNE W (B1922 (NGODU (B:s ((NsBORNIK DOKUMENTOW(B) /s - (NpOGOSQN(B, (NwARUVAN aRAMAZDOWI^ s ((NeREWAN (B:s (NlUSAKN(B,s, 2025)
(NrEZNQ ARMQN I GREKOW W sMIRNE(B, (NUSTROENNAQ TURECKIMI WOJSKAMI mUSTAFY kEMALQ aTAT@RKA W (B1922 (NG(B. (NW HODE GREKO(B-(NTURECKOJ WOJNYs
(NuKAZ(B. : (NS(B. 49-55s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B.s
Keywords: (NiSTORIQ ARMQNSKOGO NARODAs -- 19-20 (NWW(B.s; (NiSTORIQs -- (NtURCIQs -- 19-20 (NWW(B.s; (NmEVDUNARODNYE OTNO[ENIQs; (NgREKO(B-(NTURECKAQ WOJNAs -- 1919-1922 -- (NiSTO^NIKIs; (NgENOCID ARMQNSKOGO I GRE^ESKOGO NASELENIQ s -- (NtURCIQ (B((NoSMANSKAQ IMPERIQ(B)s -- (NiSTORIQs; (NsMIRNA(B, (NGOROD (B((NiZMIR(B, (NGOROD(B)s -- (NiSTORIQ s -- (NnA^(B. 20 (NW(B.s